2018
DOI: 10.1002/pen.24943
|View full text |Cite
|
Sign up to set email alerts
|

Microwave pre‐oxidation for polyacrylonitrile precursor coated with nano‐carbon black

Abstract: A surface coating was successfully applied through dipping the polyacrylonitrile (PAN) precursor fibers in a carbon black (CB) bath containing a hydrolyzed binder. The coated fibers were pre-oxidized over the microwave furnace at temperatures ranging from 100 C to 170 C for different heating times. The changes in chemical structure were studied by Fourier transfer infrared spectroscopy combined with elemental analyzer. X-ray diffraction was employed to study the crystalline structure and its related parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The inclusion of various fillers such as clay, cellulose nanocrystal, carbon allotropes, and other nanoparticles (MoS 2 , TiO 2 , Fe 3 O 4 ) into the structure of fibers has been widely conducted to modify PAN fibers [28][29][30][31][32][33][34][35][36][37][38]. For instance, PAN composite fibers containing graphene oxide (GO) have gained significant interest owing to their large surface area and the effect of the functional groups of filler, which result in appropriate interactions with polymer [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of various fillers such as clay, cellulose nanocrystal, carbon allotropes, and other nanoparticles (MoS 2 , TiO 2 , Fe 3 O 4 ) into the structure of fibers has been widely conducted to modify PAN fibers [28][29][30][31][32][33][34][35][36][37][38]. For instance, PAN composite fibers containing graphene oxide (GO) have gained significant interest owing to their large surface area and the effect of the functional groups of filler, which result in appropriate interactions with polymer [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…[17] Most recently, efforts have been devoted to making use of the microwave for the thermal stabilization of PAN precursors to avoids these problems. [18][19][20][21] To make full use of the advantages of microwave irradiations in the thermal stabilization of PAN, we need to make clear the physical picture of the interactions between the microwave and PAN. In recent years, a few molecular dynamics simulations have been done to understand the effects of microwave irradiations on relatively simple systems, such as pure water or aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Polyacrylonitrile (PAN) is a common precursor of carbon aerospace structures and is processed as follows: (i) stabilization step at 250 °C and (ii) carbonization at temperature >1200 °C under inert conditions to form graphene-like sheets. During the stabilization step, PAN chains form cyclic structures, which improve the structural integrity of the resulting carbon structure. The stabilization step involves multiple reactions including cyclization, dehydrogenation, cross-linking, and oxidation, which are often diffusion-controlled reactions …”
Section: Introductionmentioning
confidence: 99%
“…The temperature gradient for volumetric heating methods is from inside-to-outside where the core is hotter than the skin. In particular, microwave and direct current heating of PAN and its composites have been employed for this purpose. , Liu et al showed that PAN can be heated to 220 °C using a 960 W microwave furnace; this method has shown reduced energy and time consumption in the stabilization step . Elagib et al used carbon black surface coatings on PAN fibers to increase electromagnetic field absorption and stabilize PAN using microwaves.…”
Section: Introductionmentioning
confidence: 99%